Seismic Earth Pressures of Retaining Wall from Large Shaking Table Tests. (22nd March 2015) - Yang, Changwei; Zhang, Jian Jing; Honglue, Qu; Junwei, Bi; Feicheng, Liu
Abstract : To ascertain seismic response of retaining wall in the Wenchuan earthquake, large shaking table tests are performed and an acceleration record is acted in 3 directions. In the tests, acceleration time history recorded at Wolong station in the Wenchuan earthquake is used to excite the model wall. Results from the tests show that the location of dynamic resultant earth pressure is 0.35–0.49 H from toe of the wall for road shoulder retaining wall on rock foundation, 0.33–0.42 H for embankment retaining wall on rock foundation, and 0.46–0.77 H for road shoulder retaining wall on soil foundation. Besides, dynamic earth pressure increases with the increase of ground shaking from 0.1 g to 0.9 g and the relationship is nonlinear. The distribution is closed to for PGA less than 0.4 g but larger for PGA larger than and equal to 0.4 g, especially on the soil foundation. After the comparison of measured earth pressures and theoretical results by pseudodynamic method and pseudostatic method, results of the former are consistent with those of the shaking table test, but results of the latter method are smaller than measured.